Tìm x
x2-64=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
a. $(x^2-9)(5x+15)=0$
$\Rightarrow x^2-9=0$ hoặc $5x+15=0$
Nếu $x^2-9=0$
$\Rightarrow x^2=9=3^2=(-3)^2$
$\Rightarrow x=3$ hoặc $-3$
Nếu $5x+15=0$
$\Rightarrow x=-3$
b.
$x^2-8x=0$
$\Rightarrow x(x-8)=0$
$\Rightarrow x=0$ hoặc $x-8=0$
$\Rightarrow x=0$ hoặc $x=8$
c.
$5+12(x-1)^2=53$
$12(x-1)^2=53-5=48$
$(x-1)^2=48:12=4=2^2=(-2)^2$
$\Rightarrow x-1=2$ hoặc $x-2=-2$
$\Rightarrow x=3$ hoặc $x=0$
d.
$(x-5)^2=36=6^2=(-6)^2$
$\Rightarrow x-5=6$ hoặc $x-5=-6$
$\Rightarrow x=11$ hoặc $x=-1$
e.
$(3x-5)^3=64=4^3$
$\Rightarrow 3x-5=4$
$\Rightarrow 3x=9$
$\Rightarrow x=3$
f.
$4^{2x}+2^{4x+3}=144$
$2^{4x}+2^{4x}.8=144$
$2^{4x}(1+8)=144$
$2^{4x}.9=144$
$2^{4x}=144:9=16=2^4$
$\Rightarrow 4x=4\Rightarrow x=1$
Bài 1:
a) Ta có: (x2 - 36)(x2 -25)= 0
\(\Leftrightarrow\)(x2 - 62)(x2 - 52)= 0
\(\Leftrightarrow\)(x - 6)(x + 6)(x - 5)(x + 5)= 0
\(\Leftrightarrow\)\(\orbr{\begin{cases}x-6=0\\x+6=0\end{cases}}\)
\(\orbr{\begin{cases}x-5=0\\x+5=0\end{cases}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=6\\x=-6\end{cases}}\)
\(\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)
b) \(CMTT\)câu a
Ta có:\(\orbr{\begin{cases}x=7\\x=-7\end{cases}}\)
\(\orbr{\begin{cases}x=8\\x=-8\end{cases}}\)
a)16. x2 = 64
x2 = 64 : 16
x2 = 4
x2 = 22
⇒ x = 2
b) (5.x - 2) - 64 = -36
(5.x - 2) = -36 + 64
5.x - 2 = 28
5.x = 28 + 2
5.x = 30
x = 30 : 5
x = 6
c) (2x - 10).(5 - x) = 0
TH1: 2x - 10 = 0
2x = 0 + 10
2x = 10
x = 10 : 2
x = 5
TH2: 5 - x = 0
x = 5 - 0
x = 5
⇒ Vậy x = 5.
c: Ta có: \(x^3-12x^2+48x-64=0\)
\(\Leftrightarrow x-4=0\)
hay x=4
c: Ta có: \(x^3-12x^2+48x-64=0\)
\(\Leftrightarrow x-4=0\)
hay x=4
a) Ta có: x 2 = 2 2 nên x = 2.
b) Ta có: x 2 = 5 2 nên x = 5.
c) Ta có: 3 x 5 = 3 nên x 5 = 1 . Do đó x = 1.
d) Ta có: 6 x 3 = 48 nên x 3 = 8 . Do đó x = 2.
e) Ta có: x - 1 2 = 2 2 nên x - 1 = 2 . Do đó x = 3.
f) Ta có: x + 1 2 = 5 2 nên x +1 = 5. Do đó x = 4.
g) Ta có: x - 1 3 = 3 3 nên x - 1 = 3 . Do đó x = 4.
h) Ta có: x + 1 3 = 4 3 nên x +1 = 4. Do đó x = 3
a: \(\Leftrightarrow\left(x-3\right)\left(5x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=\dfrac{1}{5}\end{matrix}\right.\)
b: \(\Leftrightarrow x\left(x-1\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=1\\x=-1\end{matrix}\right.\)
\(x^2-64=0\Leftrightarrow x^2-8^2=0\)
\(\Leftrightarrow\left(x-8\right)\left(x+8\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-8=0\\x+8=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=8\\x=-8\end{matrix}\right.\)
Đs:...
thanks